Implementasi Algoritma Genetika Untuk Penjadwalan Customer Service (Studi Kasus: Biro Perjalanan Kangoroo) - Chusnah Puteri Damayanti; Rekyan Regasari Mardi Putri; Mochammad Ali Fauzi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Due to the high demand of public transport, travel agency must be ready to serve the citizen. Travel need to be ready to serve the customer; called customer service. Customer service should provide information that is precise, accurate and fast to customers. At Travel Kangaroo which owns more than 300 fleet, has two locations namely central office and branches as well as long operating hours, a responsive customer service needed to serve the customers There are various rules that must be fulfilled in making the schedule of customer service too. Thus, in this study scheduling problems solved using genetic algorithms. Genetic algorithms can solve a complex problem as well as it has wide scope. Through the examination, it was obtained the best parameters that produce the most optimal fitness value with a population size of 110, 110 and comparison generation size crossover rate and mutation rate of 0.7: 0.3. By using these parameters, scheduling customer service have optimal results, although there are violations that occur with shorter computation time compared with the manual.